Heinrich와 Bird의 도미노 이론을 이용한 철도작업자 사고 원인분석에 관한 연구 - 김성지; 이철기; 염병수; 갈원모 (한국설비안전학회지, 2022)
This paper analyzed industrial accidents that occurred during the last 5 years (2016-2020) of employees working for Korea Railroad Corporation. The purpose of this study was to analyze the causes of industrial accidents and to suggest methods for accident prevention and safe work. Nine types of disasters that have occurred over the past 5 years (jammed, fall, falling, hit, bump, Unbalanced and excessive motion, cut off· cut·stab, burn, Electric shock) were classified and analyzed. H.W.Heinrich's domino theory 3 stage, the removal cause was analyzed focusing on unsafe behavior, and Frank Bird's domino theory stage 2 4M(Man, Machine, Media, Management) technique of the basic cause of the basic cause was applied to compare the removal cause. analyzed. Most of the accidents occurred due to human causes caused by unsafe behavior or carelessness. The purpose of this study is to suggest ways to reduce industrial accidents and work safely for railroad operators.
Keywords: Industrial Accident; Heinrich domino theory; Unsafe Behavior; bird domino theory; 4M(Man; Machine; Media; Management)